Social transfers and chronic poverty : emerging evidence and the challenge ahead (Department for International Development LondonGB, 2005)
Describes the type of social transfer programmes that can currently be found in developing countries. Considers the evidence on the impact of effective social transfer schemes on chronic poverty and their role in promoting and distributing growth. Demonstrates that social transfers are affordable in even the poorest countries. Assesses some of the challenges to be faced when implementing social transfer programmes and suggests how these could be overcome.
Bibliography: p. 38-40